RESPECT: A SIMPLE METHOD TO AVOID PLAGIARISM IN EFL CONTEXT - Behnam Aghayani (International Journal of Humanity Studies (IJHS), 2021)
Academic Plagiarism, consciously or unconsciously, is on the rise and it hurts the scientific community. So, regarding the absurd nature of this academic misconduct, the present study aimed to introduce and develop a new and simple method, called RESPECT, to avoid plagiarism in EFL context. To this end, first, the reasons behind plagiarism and factors that influenced on plagiarism have been discussed. Second, all types of plagiarism have been identified and then, some important studies on plagiarism in EFL context have been reviewed. Finally, the components of RESPECT have been defined. Based on the key role of RESPECT, it would eliminate plagiarism not only in the EFL context but also in all areas of science. Moreover, it is hoped that we will no longer see the occurrence of such academic misconduct by following the strategies to avoid plagiarism in academic writings. In addition, some recommendations to avoid plagiarism have been provided at the end.